2018
DOI: 10.1590/1806-9061-2018-0782
|View full text |Cite
|
Sign up to set email alerts
|

Femur Properties of Embryo in the Layer Hybrid and Pure Breeds

Abstract: Layer hybrids are more superior in the egg yield than pure breeds. But this superiority causes some problems in the bones during the production period. There are a lot of differences among genotypes in the production period that have been examined extensively, however, the differences throughout incubation period aren't known yet. Thus, the objective of this study was to evaluate the differences in femur properties of pure breed and layer hybrid embryos during the incubation period. A total of 354 fresh hatchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…One female chick from each of the BAR-1 hens was randomly selected at the hatch, and it was sacrificed by cervical dislocation. The tibia and femur bones of chick were separated, and weight, length, and width values were determined (Onbaşılar et al, 2018;2020).…”
Section: Hatching Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One female chick from each of the BAR-1 hens was randomly selected at the hatch, and it was sacrificed by cervical dislocation. The tibia and femur bones of chick were separated, and weight, length, and width values were determined (Onbaşılar et al, 2018;2020).…”
Section: Hatching Resultsmentioning
confidence: 99%
“…The egg shell microscopic characteristics, the ash, and the Ca levels of shell were determined as explained above. The tibia and femur bones were separated and the weight, length, and width of each of the bones were determined (Onbaşılar et al, 2018;2020).…”
Section: Embryo Developmentmentioning
confidence: 99%
“…However, Mn and Cu levels of leg bones were not found to be different among the genotype groups. Onbaşılar et al (16) reported higher Zn content in the femur of embryos from hybrid type layers as compared to the pure breeds.…”
Section: Discussionmentioning
confidence: 97%